2020
DOI: 10.3389/fvets.2020.00645
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Genetic Characterization of Viruses Present in Free-Ranging Snow Leopards Using Next-Generation Sequencing

Abstract: Snow leopards inhabit the cold, arid environments of the high mountains of South and Central Asia. These living conditions likely affect the abundance and composition of microbes with the capacity to infect these animals. It is important to investigate the microbes that snow leopards are exposed to detect infectious disease threats and define a baseline for future changes that may impact the health of this endangered felid. In this work, next-generation sequencing is used to investigate the fecal (and in a few… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…As found in many other studies of fecal microbiome [37,41], many reads from small circular DNA viruses were observed in the present study, with most sequences belonging to the families Circoviridae (e.g., CRESS virus), Genomoviridae (e.g., Alces alces faeces assoc. genomovirus) and Smacoviridae (e.g., ovine faeces assoc.…”
Section: Small Circular Dna Virusessupporting
confidence: 88%
See 2 more Smart Citations
“…As found in many other studies of fecal microbiome [37,41], many reads from small circular DNA viruses were observed in the present study, with most sequences belonging to the families Circoviridae (e.g., CRESS virus), Genomoviridae (e.g., Alces alces faeces assoc. genomovirus) and Smacoviridae (e.g., ovine faeces assoc.…”
Section: Small Circular Dna Virusessupporting
confidence: 88%
“…Then 250 µL was extracted from the pool with a magnetic bead-based kit (Viral NA Extraction Kit, Diasorin, Ireland) in an Arrow extraction robot (NorDiag, Oslo, Norway). Extracted RNA in the eluted total NA was converted to cDNA using random hexamers or the FR20RV-6N primer [ 37 ] with the SuperScript IV first-strand synthesis kit (Invitrogen). Double-stranded DNA was obtained by incubation of cDNA with Klenow Fragment DNA polymerase (New England Biolabs, Ipswich, MA, USA) at 37 °C for 1 h. The Klenow enzyme was then inactivated at 75 °C for 10 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The only study on viral diseases in free-ranging snow leopards to date found that four of six sampled snow leopards had been infected by rotavirus. The study also reported infections of felid herpesvirus 1 and feline papillomavirus 2 (Johansson et al 2020b). Snow leopards from the same study area also carried antibodies against feline corona virus (Snow Leopard Trust, unpublished data).…”
Section: Snow Leopardsmentioning
confidence: 85%
“…Quantitative real-time PCR (qPCR) [37], next-generation sequencing (NGS) [38,39], enzyme-linked immunosorbent assays (ELISA) [40] are currently the most widely used "gold standard" methods, which are applied for the detection and identification of viral DNA in clinical practice [41][42][43]. Therefore, during the recent epidemic of COVID-19 [44,45], it is especially relevant to develop a new method or to adapt/optimize other specific, sensitive, rapid, inexpensive, accurate, already applicable techniques for early detection of a nucleic acid of interest in specific and environmentally friendly methods.…”
Section: Introductionmentioning
confidence: 99%